Dispersion and fate of methane emissions from cold seeps on Hikurangi Margin, New Zealand - Law, Cliff S.; Collins, Charine; Marriner, A.; Bury, Sarah J.; Brown, Julie C. S.; Rickard, Graham (Frontiers in Earth Science, 2024)
The influence of cold seep methane on the surrounding benthos is well-documented but the fate of dissolved methane and its influence on water column biogeochemistry remains less understood. To address this, the distribution of dissolved methane was determined around three seeps on the south-east Hikurangi Margin, south-east of New Zealand, by combining data from discrete water column sampling and a towed methane sensor. Integrating this with bottom water current flow data in a dynamic Gerris model determined an annual methane flux of 3 x 105 kg at the main seep. This source was then applied in a Regional Ocean Modelling System (ROMS) simulation to visualize lateral transport of the dissolved methane plume, which dispersed over ~100 km in bottom water within one year. Extrapolation of this approach to four other regional seeps identified a combined plume volume of 3500 km3 and annual methane emission of 0.4 – 3.2 x 106 kg CH4 y-1. This suggests a regional methane flux of 1.1-10.9 x 107 kg CH4 y-1 for the entire Hikurangi Margin, which is lower than previous hydroacoustic estimates. Carbon stable isotope values in dissolved methane indicated that lateral mixing was the primary determinant of methane in bottom water, with potential methane oxidation rates orders of magnitude lower than the dilution rate. Calculations indicate that oxidation of the annual total methane emitted from the five seeps would not significantly alter bottom water dissolved carbon dioxide, oxygen or pH; however, superimposition of methane plumes from different seeps, which was evident in the ROMS simulation, may have localized impacts. These findings highlight the value of characterizing methane release from multiple seeps within a hydrodynamic model framework to determine the biogeochemical impact, climate feedbacks and connectivity of cold seeps on continental shelf margins.